(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Some of the major challenges facing developing countries such as Nigeria are hunger and starvation due to the consumption of inadequate nutritive food. This ugly situation can be partially resolved, if good food rich in ascorbic acid and mineral contents are consumed. Diospyros mespiliformis is an indigenous wild-tree whose importance has not been fully explored. This study was aimed at investigating the proximate, ascorbic acid and mineral composition of the edible portion of the fruit. Matured samples of the fruit were collected from Bakiya village in Katsina state. The fruits edible portion was assessed for proximate, ascorbic acid and mineral content using standard procedure. The results obtained from the proximate analysis were (g/100g): Moisture content (13.11 ± 0.35), Crude fibre (3.37 ± 0.26), Ash content (2.20 ± 0.17), Crude fat (19.08 ± 0.46), Crude protein (6.01 ± 0.37), and Carbohydrate (56.55 ± 0.72). The mineral analyzed were (mg/100g): Copper (30.30 ± 5.833), Lead (5.063 ± 1.253), Iron (9.88 ± 2.136), Zinc (4.63 ± 2.12), Magnesium (24 ± 22.52), Calcium (69.44 ± 12.73), Sodium (14.45 ± 3.85) and Potassium (8.44 ± 4.43). The Vitamin analyzed was Vitamin C (24.56 ± 0.16 mg/100g). From the mineral analysis, Calcium is the most abundant indicating that fruit edible portion can be used for management of Oesteomalacia. The results also, indicated that Jackal berry fruit pulp could be promoted as carbohydrate and fat enhancement for rural communities. It can also serve as a raw material for juice and jam production.